2009
DOI: 10.1042/bj20090492
|View full text |Cite
|
Sign up to set email alerts
|

The respiratory complexes I from the mitochondria of two Pichia species

Abstract: NADH:ubiquinone oxidoreductase (complex I) is an entry point for electrons into the respiratory chain in many eukaryotes. It couples NADH oxidation and ubiquinone reduction to proton translocation across the mitochondrial inner membrane. Because complex I deficiencies occur in a wide range of neuromuscular diseases, including Parkinson's disease, there is a clear need for model eukaryotic systems to facilitate structural, functional and mutational studies. In the present study, we describe the purification and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 45 publications
0
32
0
Order By: Relevance
“…Complex I was prepared from Bos taurus (bovine) heart mitochondria [20], Pichia pastoris [21] and Escherichia coli [22], as described previously. SMPs (submitochondrial particles) and mitochondrial membranes were prepared from bovine heart mitochondria [20,23].…”
Section: Methodsmentioning
confidence: 99%
“…Complex I was prepared from Bos taurus (bovine) heart mitochondria [20], Pichia pastoris [21] and Escherichia coli [22], as described previously. SMPs (submitochondrial particles) and mitochondrial membranes were prepared from bovine heart mitochondria [20,23].…”
Section: Methodsmentioning
confidence: 99%
“…For some purified eukaryotic, non-mammalian enzymes the Fe:FMN ratio's are 27.5 (Torulopsis utilis (Tottmar and Ragan 1971)), 28-38 (N. crassa (Schulte et al 1998)), 33.2 (Pichia pastoris (Bridges et al 2009)) and 30.4 (Pichia angusta (Bridges et al 2009)). The values for the purified Y. lipolytica enzyme have not been reported (Djafarzadeh et al 2000;Kashani-Poor et al 2001a).…”
Section: Quantitative Aspectsmentioning
confidence: 98%
“…NUZM is fungal-specific. [13][14][15][16][17]24,25 From the Candida Genome Database, we have identified NUXM as orf19.6607 (NUO1) and NUZM as orf19.287 (NUO2). We have shown that both proteins are NADH: Ubiquinone Oxidoreductases.…”
Section: Complex I Subunit Proteins As Drug Targetsmentioning
confidence: 99%
“…These data have been rather easy to obtain, given the extensive data bases that allow comparisons across species including human mitochondria. [13][14][15][16][17] If a search focuses upon new targets for antifungal drug discovery, specificity should be an initial descriptor followed by the verification of functions of the selected gene. The latter requires mutation/deletion of the encoding gene to profile dysfunction(s), and by inference, direct or indirect functions.…”
Section: -6 Whilementioning
confidence: 99%